2021
DOI: 10.1016/j.isci.2021.102673
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-targeted hydroxyurea inhibits OXPHOS and induces antiproliferative and immunomodulatory effects

Abstract: Hydroxyurea (HU), an FDA-approved drug for treating sickle cell disease, is used as an antitumor drug alone and together with conventional chemotherapeutics or radiation therapy. HU is used primarily to treat myeloproliferative diseases because it inhibits the enzyme ribonucleotide reductase involved in DNA synthesis. The hydroxyl group in HU is considered critical for its antiproliferative and chemotherapeutic effects. Here, we substituted the hydroxyl group in HU with a triphenylphosphonium cation attached t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Mito-ATO and other mitochondria-targeted compounds (Mito-hydroxyurea and Mito-magnolol) activate T cells and inhibit regulatory T cells (T regs ) and myeloid-derived suppressor cells 29 , 61 , 62 . In addition to increasing intracellular lactate levels, AZD-3965 has pronounced effects on cancer cell metabolism (enhanced mitochondrial oxidative metabolism and improved bioenergetics).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mito-ATO and other mitochondria-targeted compounds (Mito-hydroxyurea and Mito-magnolol) activate T cells and inhibit regulatory T cells (T regs ) and myeloid-derived suppressor cells 29 , 61 , 62 . In addition to increasing intracellular lactate levels, AZD-3965 has pronounced effects on cancer cell metabolism (enhanced mitochondrial oxidative metabolism and improved bioenergetics).…”
Section: Discussionmentioning
confidence: 99%
“…Although the present data were obtained from in vitro cell culture experiments, the proposed strategy should be translatable to in vivo mouse xenografts. A related non-PEGylated analog, Mito-ATO, inhibited immunosuppressive T regs and myeloid-derived suppressor cells in bone marrow cells and another mitochondria-compound-inhibited tumor growth in immune competent mice xenografts 29 , 61 , 62 . PEGylated biopharmaceuticals, micelles, nanoparticles, and liposomes were shown to induce immunogenicity 64 .…”
Section: Discussionmentioning
confidence: 99%
“…Defects in cellular metabolic pathways underlie this feature. Cheng et al observed defective glycolysis, β-fatty acid oxidation, and OXPHOS in monocytes rendered immunotolerant in vitro [ 44 ]. These metabolic defects were evidenced by decreased lactate production, downregulated expression of fatty acid transporters CD36 and CPT1, and decreased oxygen consumption [ 45 ].…”
Section: Metabolic Dysfunction and Regulation In Sepsismentioning
confidence: 99%
“…8 Recent reports suggest that triphenylphosphonium (TPP + )-containing mitochondrial drugs inhibit tumor-suppressive cells, such as the myeloid-derived suppressor cells (MDSCs) and regulatory T cells (T regs ), in the TIME. 15,16 MDSCs suppress T cells that destroy tumor cells. 17 Targeting MDSCs and T regs is emerging as an antitumor therapeutic strategy.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Investigating the immunomodulatory effects of mitochondria-targeted drugs (MTDs), especially TPP + -based drugs, is an area of intense research. 16,22 Emerging research indicates that the TIME in Black cancer patients consists of more protumorigenic and immunosuppressive factors than in white cancer patients. 23,24 Developing potent yet nontoxic MTDs may help overcome this biological disparity.…”
Section: Introductionmentioning
confidence: 99%